Environmental legislation analysis improvement approach of global marine plastic pollution from the perspective of holistic system view - Xu, Shuqing (Frontiers in Marine Science, 2024)
Marine plastic pollution (MPP) has posed an unavoidable challenge to the conservation of marine ecosystems, escalating at an unprecedented rate. It extends beyond visible pollution, infiltrating the food chain and microcirculation, ultimately affecting the life and health of marine organisms. Of even greater concern is the fact that MPP has been found to penetrate human bloodstreams. The international community increasingly focuses on MPP, and has formulated a series of laws and regulations. This article analyses marine pollution prevention legislation within the context of international environmental resolutions and conventions, including those established by the United Nations, the European Union law and the domestic legislation of sovereign states. It is evident that the current legislation has played a pivotal role in the preventing MPP. However, global legislation on preventing MPP remains fragmented. The problems existing in the current legislation should be reviewed from the holistic systems perspective, and the integrity and systematicness of new plastics convention should be demonstrated. The proposed Marine Plastics Convention should emphasize environmental justice, protect the rights of vulnerable populations, lower the threshold for risk prevention, and focus on addressing residual risks. It must include clear provisions for regulating hydrosphere plastic pollution (HPP) to mitigate land-based pollution and scientifically define fundamental legal concepts to foster coordinated action among States. Moreover, the convention should establish standardized monitoring methodologies and assessment criteria to ensure accurate evaluation of the pollution status.